IMPLEMENTATION OF WATER VALENCE ELECTRONS BY INTERLOCKING PITCH COMBINATION METHODS IN THE PROCESS CREATING MUSICAL WORKS - Ketut Sumerjana; Ary Nugraha Wijayanto (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
Water is the source of human life both personally and communally. As a source of life, the benefits of water are very diverse, especially as a source of energy for living things, in humans, water is an important factor because it has a percentage of 70%. The magnitude of the benefits of water, turns out to have a relationship with the chemical formula, namely H2O, a compound that has perfect bonds. The concept of perfect value in the complementary chemical bonds of water provides a way to implement the value of its valence electrons by working on interlocking pitch combinations in musical compositions. The research method uses Practice Led Research with the aspect of reflection that has a relationship with practice so that the relationship consists of several stages, namely: literature study, sound synthesis, complementary experiment, evaluation and reflection. Research shows that the combination of pitch tones is part of the mathematical function of a musical series, the output of Led Research is in the form of a musical "+26"